A new era for the rural women of Nigeria - Emerole, S. M. (Jos SUM-CRC Media Services, 1991)
This publication provides an overview of the Nigerian rural women. It covers topics like: definition, classification and the life style of the rural women in Nigeria; Nigerian rural women, a huge potential for development; problems affecting rural women in Nigeria; solutions to the problems (the role of government, the role of women).
lje 28/09/16
Loans
Keywords: Rural Women; Rural Development; Gender; Nigeria